2006
DOI: 10.1111/j.1348-0421.2006.tb03773.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine GM‐CSF Genetic Adjuvant Facilitates Prophylactic DNA Vaccine against Pseudorabies Virus through Enhanced Immune Responses

Abstract: Granulocyte/macrophage colony‐stimulatory factor (GM‐CSF) is an attractive adjuvant for a DNA vaccine on account of its ability to recruit antigen‐presenting cells (APCs) to the site of antigen synthesis as well as its ability to stimulate the maturation of dendritic cells (DCs). This study evaluated the utility of GM‐CSF cDNA as a DNA vaccine adjuvant for glycoprotein B (gB) of pseudorabies virus (PrV) in a murine model. The co‐injection of GM‐CSF DNA enhanced the levels of serum PrV‐specific IgG with a 1.5‐ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 48 publications
(48 reference statements)
0
23
0
Order By: Relevance
“…Although GM-CSF has been shown to have adjuvant effects in mice (Lu et al, 2002; Wen et al, 2010; Yoon et al, 2006; Zhang et al, 2011), monkey (Loudon et al, 2010) and human studies (Jaffee et al, 2001; Luiten et al, 2005; Mastrangelo et al, 1999), there is evidence of a counteracting role in immune suppression (Kass et al, 2000). The disparate effects of GM-CSF partly depend on whether it is expressed locally at the site of immunization or systemically (Parmiani et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although GM-CSF has been shown to have adjuvant effects in mice (Lu et al, 2002; Wen et al, 2010; Yoon et al, 2006; Zhang et al, 2011), monkey (Loudon et al, 2010) and human studies (Jaffee et al, 2001; Luiten et al, 2005; Mastrangelo et al, 1999), there is evidence of a counteracting role in immune suppression (Kass et al, 2000). The disparate effects of GM-CSF partly depend on whether it is expressed locally at the site of immunization or systemically (Parmiani et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Since then other studies have shown the efficacy of GM-CSF as a vaccine adjuvant in mice (Lu et al, 2002; Wen et al, 2010; Yoon et al, 2006; Zhang et al, 2011) and NHP (Loudon et al, 2010). The use of GM-CSF has even extended to human clinical trials in which it has been used as an efficient adjuvant in cancer vaccines (Jaffee et al, 2001; Luiten et al, 2005; Mastrangelo et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, both antibody‐ and cell‐mediated immunity might play a role in protection. In reality, both enhanced humoral and cellular immunity provided effective protection against a virulent PrV challenge 17 . Furthermore, it is clear that antibodies protect against mortality after a PrV challenge 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, recombinant pertussis DNA vaccine is also valuable to prevent the infection of the pathogen. Several studies also showed that coimmunization with pGM-CSF enhanced the protection ratio of DNA vaccine (27,34). However, other studies showed GM-CSF did not improve protection (12,32).…”
Section: Discussionmentioning
confidence: 99%